Semantic based visualization: a first approach - Larrea, Martín Leonardo (2008)
Visualization is the process of mapping data into visual dimensions to create a visual representation to amplify cognition. Visual representations are essential aids to human cognitive tasks and are valued to the extent that they provide stable and external reference points upon which dynamic activities and thought processes may be calibrated and upon which models and theories can be tested and confirmed. The active use and manipulation of visual representations makes many complex and intensive cognitive tasks feasible. A visual representation is able to convey relationships among many elements in parallel and provides an individual with directly observable memory. A successful visualization allows the user to gain insight into the data, in other words to communicate different aspect of the data in an effective way. Even with today’s visualization systems that give the user a considerable control over the visualization process, it can be difficult to produce an effective visualization. To obtain useful results, a user had to know which questions to pose. Problems had to be framed in very precise terms. A strategy to improve this situation is to guide the user in the selection of the parameters involved in the visualization. Our research goal is the design of a visualization system that assist the user to do the work, by considering the semantic of the data together with the semantic of the stages through all the visualization process.